Survey of the mathematical concepts and skills needed in dressmaking - De Leon, Guillerma Co 1946- (1979)
This study aimed to determine which of the basic mathematical concepts and skills are perceived essential and necessary to the study of dressmaking in a four-year secondary curriculum. A questionnaire-checklist consisting of thirty five (35) mathematical concepts and skills was used. Responses with regards to the perceived essentiality of the concepts and skills were analyzed and ranked in terms of frequencies and corresponding percentages. Two textbooks used in dressmaking were also content-analyzed. The following mathematical concepts and skills were perceived as the most essential in dressmaking: measurement, fundamental operations with fractions and whole numbers, geometric construction, and the construction of similar figures. Operations involving decimals were considered as the least essential. The textbook content analysis showed that a mathematical base underlies the dressmaking emphasis, with focus on the four fundamental operations of addition, subtraction, multiplication, and division; measurement; applied geometry; ratio, proportion, and percentage; and conversions and simplifications, respectively ranked according to their importance in books.